THE INFLUENCE OF A GENDER IDENTITY OF AN ADDRESSEE ON THE STRUCTURE AND LANGUAGE FEATURES OF THE BUSINESS LETTER IN THE FIRST HALF OF THE XIX CENTURY (THE CASE OF BUSINESS CORRESPONDENCE BY A. S. PUSHKIN) - V. M. Kuchugurova (Гуманитарные и юридические исследования)
The author deals conditionality of structural and linguistic characteristics of a business letter by factor of gender identity and gender self-identification in the first half of XIX century. Analysis of official correspondence of A.S. Pushkin and N.A. Durova proves aspiration to achieve psychological comfort in intercourse even in the area of higher communicative functions.